(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The present study was planned to evaluate the response of broiler chicks to diets containing graded levels of spearmint (Mentha spicata). A total of 200 , five days-old, unsexes (cob) broiler chicks were used. Chicks were weighed individually and assigned randomly to five groups of 40 chicks per treatment and each treatment was subdivided to four replicates of 10 chicks each. Five experimental diets were formulated (A, B, C, D and E) to meet the nutrient requirements of broiler chicks. The experimental parameters examined were growth performance, serum metabolite, electrolyte and enzyme activities and economic appreciable. Diet (A) Negative Control (NC), a basal diet without antibiotic or spearmint, diet B as Positive Control (PC) basal diet supplemented with antibiotic (Neomycin 16 mg/Kg), diets C,D and E were basal diet supplemented with spearmint at levels of 1,1.5,and 2%, respectively. Result obtained showed that addition of spearmint improved significantly (P<0.05) the performance (body weight gain and feed conversion ratio) of broiler chicks compared to group fed on NC while no significant (P<0.05) differences between chicks fed on diets supplemented with spearmint and PC group observed, no significantly difference was found in feed consumption between all treated groups. The mortality rate did not influenced by the dietary treatments. Results revealed no significant differences (P<0.05) observed among all treatment groups in the carcass dressing percentages, Supplementation of broiler diets with spearmint at various levels was resulted in significant (p>0.05) reduction of abdominal fat, serum cholesterol, and AST enzyme activity compared to both NC and PC groups while the levels of urea, total protein, glucose and ALP and serum electrolytes levels remained unchanged. The highest profitability ratio (1.13) was obtained from the diet (E) supplemented with 2% spearmint. This study showed that spearmint when added as growth promoter in broiler diets has a similar effect on performance as that of antibiotic without any adverse effects.